About effect of the potential and the gas pressure in the vacuum chamber on the intensity of the substrate surface ion sputtering titanium and zirconium - Столбовой, Вячеслав Александрович (Eastern-European Journal of Enterprise Technologies, 2009)
The problems associated with cleaning the surface of the substrate by ion bombardment of titanium and zirconium by vacuum-arc method are considered. It is shown that the clean substrates before application of vacuum-arc coatings must be performed in a high vacuum (pressure of not more than 0.004 Pa) at a negative potential of at least 900 V